Endless loop tachycardia below the upper tracking rate of a pacemaker: A case report - Atsushi Sakamoto; Ryosuke Takeuchi; Natsuko Hosoya; Shigetaka Kageyama; Jun Kajihara; Kosuke Takahashi; Takashi Kurabe; Koichiro Murata; Ryuzo Nawada; Tomoya Onodera; Akinori Takizawa; Ryota Nomura; et al. (Journal of Arrhythmia, 2012)
An 82-year-old female with a history of hypertrophic cardiomyopathy (HCM), sick sinus syndrome (SSS), and an implanted DDD pacemaker was admitted to our hospital for congestive heart failure caused by rapid atrial fibrillation. After administration of amiodarone, atrial fibrillation (AF) became atrial flutter (AFL). Electrophysiological investigation revealed counterclockwise AFL. Catheter ablation of the cavotricuspid isthmus was performed. Burst pacing from the coronary sinus ostium to confirm the block line of the isthmus induced rapid, regular, ventricular pacing at a rate of 110 bpm. The differential diagnosis of this tachycardia included ectopic atrial tachycardia and pacemaker-mediated, endless loop tachycardia (ELT). We diagnosed this arrhythmia as ELT, because temporary reprogramming of the pacemaker mode from DDD to VVI terminated the tachycardia. In this patient, pacing parameters favored ELT (long atrioventricular delay [AVD] and short postventricular atrial refractory period [PVARP]), and atrioventricular and ventriculoatrial conduction time was prolonged as a result of amiodarone administration. The ELT continued because the rate was lower than the programmed upper tracking rate. Reprogramming the parameter (decreasing AVD and increasing PVARP) resulted in termination of ELT.